(untitled) (Human Factors in Design, 2022)
This literature review article seeks to denote the designer’s responsibilities regarding child interaction with artifacts. Links are considered between authors who have discussed interaction as a means of building knowledge and recent research addressing sensory-motor perception, emotion, signification and experience. Child’s games and artifacts become valuable resources to inclusive education, promoting an experience of active connection to the world through the sensorial so as to achieve assimilation, communication and sociocultural identification. It is intended to further the debate about perception in design, connecting research and methods for a positive experience in affective relationships, identity construction and intellectual repertoire.